(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is the research model in a planned form, according to educational standards, according to the requirements of the general economy. The teacher of the group who trained on the program (8) was a female teacher in the control group who did not come from the program, after verifying the equivalence of the two groups in variables (number of courses, academic achievement, pre-educational enlightenment scale / for parity purposes). As the researcher built the proposed program according to the requirements of the knowledge economy involved, the researcher adopted the design, which is theoretically based on the construction of four stages as well as the feedback phase. Then the researcher prepared the requirements for the experiment that included the proposed program, and in order to achieve the goal of the research and test its hypotheses, the researcher prepared the research tool: The first is the scientific enlightenment scale consisting of (60) items divided into three domains (cognitive, skill and emotional) The experiment was applied during the period from (2/1/2020) until (1/22/2020), and after the end of the experiment, the search tool was applied, and the results were shown, recommendations were given, and proposals were made.